1977
DOI: 10.1017/s0033291700018250
|View full text |Cite
|
Sign up to set email alerts
|

‘Dieters’ and ‘vomiters and purgers’ in anorexia nervosa

Abstract: SynopsisThirty-one females with primary anorexia nervosa were studied by means of a retrospective analysis of hospital notes. The patients were divided into 2 groups. The first group consisted of subjects who had become emaciated solely because of dieting, food refusal and excessive exercising (‘dieters’); the second of those who had used additional means to bring about weight loss such, as habitual vomiting and the abuse of purgatives (‘vomiters and purgers’).Most ‘dieters’ were intense, introverted, socially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
3
3

Year Published

1980
1980
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(129 citation statements)
references
References 7 publications
10
113
3
3
Order By: Relevance
“…Higher rates of normalization are reported by Meyer (1961), Farquharson & Hyland (1966), Goetz et al (1977) and Ziolko (1978). Bhanji & Thompson (1974), Beumont et al (1976) and Petzold (1979) all present lower figures. Inspection of the studies reveals further that the higher rates are associated with longer follow-up periods, and the lower percentages with shorter periods.…”
Section: General Descriptionmentioning
confidence: 62%
See 1 more Smart Citation
“…Higher rates of normalization are reported by Meyer (1961), Farquharson & Hyland (1966), Goetz et al (1977) and Ziolko (1978). Bhanji & Thompson (1974), Beumont et al (1976) and Petzold (1979) all present lower figures. Inspection of the studies reveals further that the higher rates are associated with longer follow-up periods, and the lower percentages with shorter periods.…”
Section: General Descriptionmentioning
confidence: 62%
“…Similar differences, ranging from 3% to 83%, are reported for the frequency of obsessive-compulsive symptoms and personality traits associated with anorexia nervosa. Sturzenberger et al (1977), Cantwell et al (1977), Beumont et al (1976) and Meyer (1961) all furnish high estimates, while the lowest come again from Dally & Sargant (1966) and Kay (1953).…”
Section: General Descriptionmentioning
confidence: 94%
“…But individual patients may suffer with differing subtypes during the course of their illness. [89][90][91][92] While the impact of DSM-IV AN typology on attention, memory and psychomotor functioning is not known, this study did not specifically explore this, in order to maximize the study's power and limit type II errors.…”
Section: Resultsmentioning
confidence: 99%
“…2,[6][7][8] The relationship between religion and eating disorders is also not to be underestimated, given its complexity. 9,10 The existence of eating disorders and abnormal eating attitudes in South Africa are well established in adolescents of culturally and ethnically diverse backgrounds, [11][12][13][14][15] although the prevalence thereof is currently unknown. 16 International studies have found disturbances of this nature to be more prevalent in Jewish adolescent girls and women than in their non-Jewish counterparts.…”
Section: Introductionmentioning
confidence: 99%